PENERAPAN PENDEKATAN GUIDANCE IN ACTIONS UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN GURU SD NEGERI 2 TOJAN - KETUT AGUS WIJAYA (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This research is motivated by the low ability of teachers at SD Negeri 2 Tojan, in preparing operational learning implementation plans, with the aim of research to improve the ability of teachers to prepare operational lesson plans. The research was carried out at SD Negeri 2 Tojan in the academic year 2021/2022, with 8 teachers as the subject, while the object of the research was to increase the ability of teachers to prepare operational lesson plans by applying the Guidance in Actions approach. The research follows the school's action research flow with two cycles, each cycle includes planning, action, observation and evaluation, and reflection. The data collection technique uses observation, and the data collection instrument uses an observation format. The data analysis method used a univariate descriptive statistical method, and to draw conclusions used a qualitative descriptive method. The indicator of success was the average value of the teacher's ability to prepare operational lesson plans of at least 85 with a minimum completeness of 80% . The results showed that the teacher's ability to prepare operational lesson plans had increased as evidenced by an increase from the pre-cycle average of 55.56 in the first cycle the average was 74.65 and in the second cycle the average was 86.11 and the percentage of completeness in the pre-cycle was 47.62, the first cycle was 80.00, and the second cycle 81.90. ABSTRAKPenelitian ini dilatarbelakangi rendahnya kemampuan guru SD Negeri 2 Tojan, menyusun rencana pelaksanaan pembelajaran operasional, dengan tujuan penelitian untuk meningkatkan kemampuan guru menyusun RPP operasional. Penelitian dilaksanakan di SD Negeri 2 Tojan tahun pelajaran 2021/2022, dengan subyek guru berjumlah 8 orang, sedangkan obyek penelitian peningkatan kemampuan guru menyusun RPP operasional dengan penerapan pendekatan Guidance in Actions. Penelitian mengikuti alur penelitian tindakan Sekolah dengan dua siklus masing-masing siklus meliputi perencanaan, tindakan, observasi dan evaluasi, serta refleksi. Teknik pengumpulan data menggunakan observasi, dan instrument pengumpulan datanya menggunakan format observasi. Metode analisis data menggunakan cara statistic deskriptif, dan untuk menarik kesimpulan digunakan metode deskriptif kualitatif.Indikator keberhasilan adalah nilai rerata kemampuan guru menyusun RPP operasional minimal 85 dengan ketuntasan minimal 80%. Hasil penelitian menunjukkan bahwa kemampuan guru menyusun RPP operasional mengalami peningkatan dibuktikan dengan peningkatan dari prasiklus rerata 55,56 pada siklus pertama rerata 74,65 dan di siklus kedua rerata 86,11 serta prosentase ketuntasan pada prasiklus 47,62, siklus pertama 80,00, dan siklus kedua 81,90.